Email consultations between patients and doctors in primary care: content analysis - Atherton, H; Boylan, A-M; Eccles, A; Fleming, J; Goyder, CR; Morris, RL (JMIR Publications, 2020)
Background: Increasingly, consultations in health care settings are conducted remotely using a range of communication technologies. Email allows for 2-way text-based communication, occurring asynchronously. Studies have explored the content and nature of email consultations to understand the use, structure, and function of email consultations. Most previous content analyses of email consultations in primary care settings have been conducted in North America, and these have shown that concerns and assumptions about how email consultations work have not been realized. There has not been a UK-based content analysis of email consultations. Objective: This study aims to explore and delineate the content of consultations conducted via email in English general practice by conducting a content analysis of email consultations between general practitioners (GPs) and patients. Methods: We conducted a content analysis of anonymized email consultations between GPs and patients in 2 general practices in the United Kingdom. We examined the descriptive elements of the correspondence to ascertain when the emails were sent, the number of emails in an email consultation, and the nature of the content. We used a normative approach to analyze the content of the email consultations to explore the use and function of email consultation. Results: We obtained 100 email consultations from 85 patients, which totaled 262 individual emails. Most email users were older than 40 years, and over half of the users were male. The email consultations were mostly short and completed in a few days. Emails were mostly sent and received during the day. The emails were mostly clinical in content rather than administrative and covered a wide range of clinical presentations. There were 3 key themes to the use and function of the email consultations: the role of the GP and email consultation, the transactional nature of an email consultation, and the operationalization of an email consultation. Conclusions: Most cases where emails are used to have a consultation with a patient in general practice have a shorter consultation, are clinical in nature, and are resolved quickly. GPs approach email consultations using key elements similar to that of the face-to-face consultation; however, using email consultations has the potential to alter the role of the GP, leading them to engage in more administrative tasks than usual. Email consultations were not a replacement for face-to-face consultations.